2009
DOI: 10.1177/1555412009354728
|View full text |Cite
|
Sign up to set email alerts
|

Games for Civic Learning: A Conceptual Framework and Agenda for Research and Design

Abstract: Scholars, educators, and media designers are increasingly interested in whether and how digital games might contribute to civic learning. However, there are three main barriers to advancing understanding of games' potential for civic education: the current practices of formal schooling, a dearth of evidence about what kinds of games best inspire learning about public life, and divergent paradigms of civic engagement. In response, this article develops a conceptual framework for how games might foster civic lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 26 publications
(21 reference statements)
0
55
0
2
Order By: Relevance
“…Habgood et al (2005) have suggested that the immersive state of flow may inhibit metacognition and therefore may be better suited to practicing and proceduralizing knowledge than acquiring or reflecting on it. Some kinds of learning, such as moral and civic reasoning, likely require both empathetic identification with others and critical distance from them (Raphael et al, 2010). Does social gameplay exacerbate the difficulty of reflection in the flow state by adding social-oriented diversions to the learning experience or does the social element help keep learners on task, as found in some classroom studies cited above?…”
Section: Learningmentioning
confidence: 97%
“…Habgood et al (2005) have suggested that the immersive state of flow may inhibit metacognition and therefore may be better suited to practicing and proceduralizing knowledge than acquiring or reflecting on it. Some kinds of learning, such as moral and civic reasoning, likely require both empathetic identification with others and critical distance from them (Raphael et al, 2010). Does social gameplay exacerbate the difficulty of reflection in the flow state by adding social-oriented diversions to the learning experience or does the social element help keep learners on task, as found in some classroom studies cited above?…”
Section: Learningmentioning
confidence: 97%
“…Such civic skills and characteristics, include critical thinking and the ability to assess, analyse and reflect on information and practices, organizational skills to develop networks and collaborations, communication and negotiation skills to empower collaboration, problem-solving and strategizing and visioning skills to intervene in the transformations of the public domain (Erentaitė et al, 2012;mcLeod, 2000;montgomery et al, 2004). These potential learning outcomes are connected with the empowerment and spread of basic democratic principles, such as direct and free participation in the public domain, making free and informed choices, collective decision-making and action and mutual understanding and respect for the other, which are becoming even more relevant in a globalized, networked and interactive environment (Amiel & Reeves, 2008;Hooghe & dassonneville, 2011;Kahne, 2008;Raphael et al, 2010). The interconnection of civic education with democratic principles and globalization will be further explored in the next few paragraphs.…”
Section: Civic Educationmentioning
confidence: 98%
“…Online games are engaging for young adults, offering them greater levels of discourse and creativity that they would not experience within traditional learning environments (Raphael, Bachen, Lynn, Baldwin-Philippi, & mcKee, 2010). Other researchers argue that online gaming also bridges the gap between formal and informal education and connect the latter to individuals' personal experiences, while supporting the development of their interpersonal skills (Ito et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Civic engagement and citizen participation can be broadly defined as the sum of political and social practices, by which individuals engage with and influence public affairs, beyond their direct private environment (Gordon, Balwin-Philippi, & Balestra, 2013;Parés & March, 2013;Raphael, Bachen, Lynn, Balwin-Philippi, & McKee, 2010). Engagement and participation has become an inherent part of urban planning and governance, and is facilitated by different tools and methods, well beyond its traditional expressions of voting and attending town hall meetings (Gordon & Mihailidis, 2016).…”
Section: Serious Games and Gamified Applications In Participatory Plamentioning
confidence: 99%